Atmospheric moisture pathways of East Africa and implications for water recycling at Mount Kilimanjaro - Benjamin Schumacher; Marwan Katurji; Hanna Meyer; Tim Appelhans; Insa Otte; Thomas Nauss (International Journal of Climatology, 2020)
The Mt. Kilimanjaro ecosystem depends on atmospheric moisture transport and recycling of water, yet limited knowledge on the relation between advective moisture pathways and local water recycling is available. This study uses a regional atmospheric model to analyse moisture source and sink processes as well as precipitation recycling at Mt. Kilimanjaro. The results indicate that locally produced precipitation is deposited mainly in June and July while trans‐regional effects are weak. Results also revealed the importance of tropical storm systems for local convection in the Kilimanjaro region and the effect of the Indian Ocean Zonal Mode phases on East African moisture pathways. The analysis further revealed connections between the Madagascar tip jet and the Turkana jet with implications for regional moisture pathways that have not been described before.

A glimpse at short-term controls of evapotranspiration along the southern slopes of Kilimanjaro - Florian Detsch; Insa Otte; Tim Appelhans; Thomas Nauss (Environmental Monitoring and Assessment, 2017)

Nitrogen turnover and greenhouse gas emissions in a tropical alpine ecosystem, Mt. Kilimanjaro, Tanzania - Adrian Gütlein; Marcus Zistl-Schlingmann; Joscha Nico Becker; Natalia Sierra Cornejo; Florian Detsch; Michael Dannenmann; Tim Appelhans; Dietrich Hertel; Yakov Kuzyakov; Ralf Kiese (Plant and Soil, 2017)

Eco‐meteorological characteristics of the southern slopes of Kilimanjaro, Tanzania - Tim Appelhans; Ephraim Mwangomo; Insa Otte; Florian Detsch; Thomas Nauss; Andreas Hemp (International Journal of Climatology, 2016)
This study introduces the set‐up of a new meteorological station network on the southern slopes of Kilimanjaro, Tanzania, since 2010 and presents the recorded characteristics of air temperature, air humidity and precipitation in both a plot‐based and area‐wide perspectives. The station set‐up follows a hierarchical approach covering an elevational as well as a land‐use disturbance gradient. It consists of 52 basic stations measuring ambient air temperature and above‐ground air humidity and 11 precipitation measurement sites, with recording intervals of 5 min. With respect to precipitation observations, the network extends the long‐term recordings of A. Hemp who has installed and maintained up to 117 multi‐month accumulating rainfall buckets in the region since 1997. The meteorological characteristics of the study region based on the derived data since 2010 are mostly in line with previous studies, although we see increased precipitation amounts at higher elevations during these years when compared with long‐term means. We furthermore identify a mean annual condensation level at about 2300 m a.s.l. which has not been reported before. Finally, this is the first study to provide high resolution maps of mean monthly and mean annual temperature, humidity and precipitation for Kilimanjaro, which are of great value for geographically oriented meteorological or ecological investigations. Detailed performance statistics of the geo‐statistical and machine learning techniques used for the gap filling of the recorded meteorological time series and their regionalization to the Kilimanjaro region indicate that the presented data sets provide reliable measurements of the meteorological reality at Kilimanjaro.

Temperature versus resource constraints: which factors determine bee diversity on M ount K ilimanjaro, T anzania? - Alice Classen; Marcell K. Peters; William J. Kindeketa; Tim Appelhans; Connal D. Eardley; Mary W. Gikungu; Andreas Hemp; Thomas Nauss; Ingolf Steffan‐Dewenter (Global Ecology and Biogeography, 2015)
Aim Understanding the mechanisms controlling variation in species richness along environmental gradients is one of the most important objectives in ecology. Resource availability is often considered as the major driver of animal diversity. However, in ectotherms, temperature might play a predominant role as it modulates metabolic rates and the access of animals to resources. Here, we investigate the relative importance of resource availability and temperature in determining the diversity pattern of bees along a 3.6‐km elevational gradient. Location M ount K ilimanjaro, T anzania. Methods We assessed bee species richness and abundance with pan traps and floral resources with transect records on 60 study sites which were equally distributed over six near‐natural and six disturbed habitat types along an elevational gradient from 870 to 4550 m a.s.l. We used path analysis to disentangle the effects of temperature, precipitation, floral resource abundance, bee abundance and land use on bee species richness. In addition, we monitored flower visitation rates during transect walks at different elevations to evaluate the temperature dependence of bee–flower interactions. Results Bee species richness continuously declined with elevation in natural and disturbed habitats. While the abundance of floral resources had a significant but only weak effect on species richness, the effect of temperature was strong. Temperature had a strong positive effect on species richness that was not mediated by bee abundance and an indirect effect via bee abundances. We observed higher levels of bee–flower interactions at higher temperatures, supporting the hypothesis that temperature limits diversity by constraining resource exploitation in ectotherms. Main conclusions Temperature and the availability of resources shape species richness patterns along environmental gradients. In ectothermic organisms like bees temperature seems to have the more important role, as it both limits the access to resources (abundance‐mediated effect) and accelerates other (abundance‐independent) ecological and evolutionary processes that drive the maintenance and origination of diversity.

Synoptic and climatological controls of particulate matter pollution in a Southern Hemisphere coastal city - Tim Appelhans; Andrew Sturman; Peyman Zawar‐Reza (International Journal of Climatology, 2013)
A complex interaction of local meteorology and source characteristics regularly leads to nocturnal smog events during winter in Christchurch, New Zealand. The main focus of this article is on improving understanding of the relationship between atmospheric processes operating at a range of scales that leads to poor air quality in such urban environments. This research therefore aims to provide a quantitative analysis of atmospheric influences on particulate matter pollution in Christchurch across a wide range of spatial and temporal scales, from local to hemispheric and daily to interannual. The probability of exceeding the National Environmental Standard for PM 10 for a range of local atmospheric conditions is calculated using the classification and regression trees technique, and links between these probabilities, local meteorology and synoptic weather situations are established. The effect of the transition between synoptic types on local air quality is also examined, and the progression of anticyclones across the country is identified to be the dominant synoptic control mechanism. It is shown that variation in latitudinal location of the path of anticyclones over New Zealand influences the predicted exceedance probability. On interdecadal and hemispheric scales, it is found that the particular combination of local and synoptic atmospheric conditions that favours air quality degradation shows a reoccurring pattern of frequency maxima (and minima) with a periodicity of approximately 14‐16 years. In relation to the identified interdecadal variability of synoptic circulation, a close relationship to Southern Hemisphere pressure anomalies at high latitudes is revealed. The results of this research show that, in addition to daily weather variation, air quality in Christchurch is influenced by longer‐term climatic processes that operate on interannual hemispheric scales with the implication that, in general, air pollution potential can also be expected to vary on a periodic interdecadal time scale. Copyright © 2012 Royal Meteorological Society